2021
DOI: 10.1111/his.14558
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learnt from MDM2 fluorescence in‐situ hybridisation analysis of 439 mature lipomatous lesions with an emphasis on atypical lipomatous tumour/well‐differentiated liposarcoma lacking cytological atypia

Abstract: Aims Amplification of the murine double minute‐2 (MDM2) gene, which is usually detected with fluorescence in‐situ hybridisation (FISH), is the key driving event for atypical lipomatous tumours (ALTs)/well‐differentiated liposarcomas (WDLs). We sought to determine the concordance between the histopathological findings and MDM2 FISH in the diagnosis of ALT/WDL, and to identify the histological features of MDM2‐amplified tumours lacking classic atypia. Methods and results We performed a retrospective analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…This emphasizes that FISH remains the ideal technique for detecting this genetic alteration. In a recent series of adipocytic tumor cases reported in a study by Vargas et al [113], later confirmed by Machado et al [103], instances of well-differentiated liposarcomas with isolated nuclear atypia were identified. Despite this, they exhibited immunohistochemical expression for MDM2/CDK4 and p16, alongside confirmation of MDM2 amplification by FISH [103,113].…”
Section: Implications Of Detecting Isolated Mdm2-cdk4-gli1 Alteration...mentioning
confidence: 76%
See 3 more Smart Citations
“…This emphasizes that FISH remains the ideal technique for detecting this genetic alteration. In a recent series of adipocytic tumor cases reported in a study by Vargas et al [113], later confirmed by Machado et al [103], instances of well-differentiated liposarcomas with isolated nuclear atypia were identified. Despite this, they exhibited immunohistochemical expression for MDM2/CDK4 and p16, alongside confirmation of MDM2 amplification by FISH [103,113].…”
Section: Implications Of Detecting Isolated Mdm2-cdk4-gli1 Alteration...mentioning
confidence: 76%
“…In a recent series of adipocytic tumor cases reported in a study by Vargas et al [113], later confirmed by Machado et al [103], instances of well-differentiated liposarcomas with isolated nuclear atypia were identified. Despite this, they exhibited immunohistochemical expression for MDM2/CDK4 and p16, alongside confirmation of MDM2 amplification by FISH [103,113]. Similar situations can arise in neoplasms with GLI1 alterations (Figure 6), where immunohistochemistry for GLI1 is not always sufficient, necessitating molecular confirmation [104][105][106][107][108].…”
Section: Implications Of Detecting Isolated Mdm2-cdk4-gli1 Alteration...mentioning
confidence: 76%
See 2 more Smart Citations
“…Considering the clinical consequences of misdiagnosing these lesions, the molecular analysis of MDM2 is essential, and it is usually performed with Fluorescence In Situ Hybridization (FISH) [ 30 ]. Indeed, the MDM2 amplification evaluation by FISH is a crucial and well-established assay for liposarcoma diagnostic work-up and, nowadays, is considered as a diagnostic gold standard [ 31 , 32 , 33 ]. However, despite its diagnostic relevance, no definitive consensus has ever been defined for determining the MDM2 gene status.…”
Section: Introductionmentioning
confidence: 99%